The Relationship between Age and Working Period with the Incidence of Myalgia in Mojokerto City : Original Research - Ksatria, Abdillah Budi (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Myalgia is a common complaint among many workers, especially in the informal sector. This study aims to analyze the relationship between age and work duration with the incidence of myalgia in patients at Puskesmas Wates, Kota Mojokerto. Methods: This quantitative research collected data through questionnaires filled out by respondents. Data analysis was conducted using statistical tests to examine the relationship between variables. Results: The results showed a significant relationship between age and the incidence of myalgia with a p-value of 0.035, indicating that patients aged ≥45 years had a higher prevalence of myalgia, with 25 samples. Additionally, a higher incidence of myalgia was found among workers with a work duration of ≥20 years, with 21 respondents experiencing high myalgia and a p-value of 0.014. Patients aged ≥45 years had a 6.571 times greater risk of experiencing high myalgia compared to patients aged <45 years, while patients with a work duration of ≥20 years had an 11.667 times higher risk compared to those with a work duration of <20 years. Conclusions: These conclusions highlight the importance of paying special attention to age and work duration factors in efforts to prevent and manage myalgia among workers.